Pengaruh AI-Powered Recommendation dan Live Streaming terhadap Keputusan Pembelian di Tiktok Shop dengan Customer Trust sebagai Variabel Mediasi - I Gede Satiya Brana Waja; Ketut Tanti Kustina (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Consumer buying habits have changed as a result of the growth of social commerce, especially with TikTok Shop's interactive features like live streaming and AI-powered recommendations. However, there are still conflicting scientific results about their efficacy and the significance of trust. The purpose of this study is to investigate how AI-powered recommendations and live streaming affect consumers' decisions to buy, using customer trust as a mediating factor among Generation Z consumers in Denpasar City. Purposive sampling was used in a quantitative study design with 144 participants who had previously made purchases on TikTok Shop after viewing live streaming sessions and getting AI-based suggestions. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to examine the data. The findings demonstrate that while live streaming has a favorable and considerable impact on purchasing decisions, AI-powered recommendations have a positive but negligible effect. Live streaming and AI-powered recommendations both greatly increase consumer trust. It's interesting to note that the relationship between independent variables and purchase decisions is weakened by consumer trust, which has a negative and significant impact on decisions. These results imply that while personalization and interaction enhance the user experience, trust does not always result in instantaneous purchases. The study emphasizes the necessity of increased authenticity and transparency in social commerce to guarantee that trust serves as a motivator rather than a hindrance to purchasing decisions.